An Immune Model to Predict Prognosis of Breast Cancer Patients Receiving Neoadjuvant Chemotherapy Based on Support Vector Machine - Wang, Mozhi; Pang, Zhiyuan; Wang, Yusong; Cui, Mingke; Yao, Litong; Li, Shuang; Wang, Mengshen; Zheng, Yanfu; Sun, Xiangyu; Dong, Haoran; Zhang, Qiang; Xu, Yingying (Frontiers in Oncology, 2021)
Tumor microenvironment have been increasingly proved to be crucial during the development of breast cancer. The theory about the conversion of cold and hot tumor attracted the attention to the influences of traditional therapeutic strategies on immune system. Various genetic models have been constructed, though the relation between immune system and local microenvironment still remains unclear. In this study, we tested and collected the immune index of 262 breast cancer patients before and after neoadjuvant chemotherapy. Five indexes were selected and analyzed to form the prediction model, including the ratio values between after and before neoadjuvant chemotherapy of CD4+/CD8+ T cell ratio, lymphosum of T cell, B cell and NK cell, CD3+ CD8+ cytotoxic T cell percent, CD16+CD56+ NK cell absolute value and CD3+ CD4+ helper T cell percent. Interestingly, these characters are both the ratio value of immune status after neoadjuvant chemotherapy to the baseline. Then the prediction model was constructed by support vector machine (accuracy rate = 75.71%, area under curve = 0.793). Beyond the prognostic effect and prediction significance, the study instead emphasized the importance of immune status in traditional systemic therapies. The result provided new evidence that the dynamic change of immune status during neoadjuvant chemotherapy should be paid more attention.